Testing the validation of the financial cooperation agreement among ASEAN+3 stock markets - Rahman, Md. Saifur; Othman, Anwar Hasan Abdullah; Shahari, Farihana (Emerald Group Publishing Ltd., 2017)
Purpose: The purpose of this paper is to investigate the validation of the ASEAN+3 financial cooperation agreement among its members. In particular, it examines the long- and short-run relationships among the stock market indices of eight countries: China (CH), Japan (JP),Korea (KR), Malaysia (MY), Indonesia (ID), Philippines (PH), Thailand (TH), and Singapore (SG). Design/methodology/approach: The study applied a global VAR and vector error correction model (VECM) model to investigate this relationship using daily data over the period from first March 1992 to end of September 2013. The study period has been separated into pre-1997/1998 financial crisis period (1992-1997) and post-1997/1998 crisis period (1999-2013). Findings: The findings show that the stock markets in the ASEAN region are integrated during both periods of financial crises. However, the markets are moving toward better integration, particularly during the post-crisis period. This is supported by the results of the error correction which indicated that most ASEAN+3 stock market indices adjust quickly within the short run to a shock in the long-run equilibrium relationships in the region during both the pre- and post-crisis periods. In addition, the results of the VECM causality test showed that a short-run relationship exists among the ASEAN+3 stock market indices. Practical implications: The results of this study therefore have two implications: first, for investors in terms of construction of the portfolio diversification strategies across difference stock markets in Asian region, and second, for policy makers, as the study presents an understanding of financial exposure in their countries as consequences of changes that occur in the other stock market indices in the ASEAN region. Social implications: The investors can find the potential sectors for the portfolio investments. Originality/value: The paper is one of the pioneers to examine the validity of ASEAN+3 financial cooperation agreement. © 2017, © Emerald Publishing Limited.